PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 003 TELUKNILAP KECAMATAN KUBU - Fakhriza '; Zulkifli '; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aims to improve student learning outcomes through theimplementation of IPS cooperative learning model Number Heads Together(NHT) in Class V Elementary School 003 Gulf Nilap Kubu district 2013l2014academic year. This research was conducted in April to June 2014 the number of34 students, 20 boys and 14 girls. The results of the first cycle of observationshowed good activity has started 16 teachers (66.66%) in accordance with theplan, to observation of teacher activity at the second meeting considered either 18(75%). For the second cycle of activity observed with the category of teachers hasincreased very well 22 (91.66%) and in accordance with the plan, to aobservasiteacher activity at the second meeting of the second cycle also increases the verygood category 23 (95.83%). While the observation of student activity is good alsoat the first meeting of 16 (66.66%) and at the second meeting of 18 (75%) In thesecond cycle of observation of student activity increases with category very well22 (91.66) and also activity increases with category students very well at the lastmeeting 23 (95.83%). Based on the analysis of data from the discussion, theaverage value of the basic scores of students before the implementation ofcooperative learning model Number Heads Together (NHT) is 63.66. Thenincreased to 71.88 in the first cycle and increased again in the second cycle is83.82 thus it can be concluded that with the implementation of cooperativelearning model Number Heads Together (NHT) can improve learning outcomesIPS Elementary School fifth grade students 003 Gulf Nilap Kubu district.Keywords: Numbereds Heads Together, IPS Learning Outcomes